2019
DOI: 10.3390/ijerph16152701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epiphytes and Depth on Seagrass Spectral Profiles: Case Study of Gulf St. Vincent, South Australia

Abstract: Seagrasses are a crucial indicator species of coastal marine ecosystems that provide substratum, shelter, and food for epiphytic algae, invertebrates, and fishes. More accurate mapping of seagrasses is essential for their survival as a long-lasting natural resource. Before reflectance spectra could properly be used as remote sensing endmembers, factors that may obscure the detection of reflectance signals must be assessed. The objectives in this study are to determine the influence of (1) epiphytes, (2) water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Hwang et al reported "Effects of Epiphytes and Depth on Seagrass Spectral Profiles: Case Study of Gulf St. Vincent, South Australia" [5]. The objectives in this study are to determine the influence of (1) epiphytes, (2) water depth, and (3) seagrass genus on the detection of reflectance spectral signals.…”
Section: The Topics Of Environmental Health Sciences and Public Healthmentioning
confidence: 99%
“…Hwang et al reported "Effects of Epiphytes and Depth on Seagrass Spectral Profiles: Case Study of Gulf St. Vincent, South Australia" [5]. The objectives in this study are to determine the influence of (1) epiphytes, (2) water depth, and (3) seagrass genus on the detection of reflectance spectral signals.…”
Section: The Topics Of Environmental Health Sciences and Public Healthmentioning
confidence: 99%
“…For instance, given the similar spectral response, the class turbidity may include turbid-waters environments, sandy bottoms, and sparse macrophyte areas. In addition, epiphytes (organisms growing on the surface of plants) and water depth may increase the uncertainty of seabed classification by modifying the spectral reflectance response of seagrass and algae (Hwang et al, 2019). It is needed to improve truth data classification (i.e., get more field data and increase the number of classes).…”
Section: Discussionmentioning
confidence: 99%
“…In the Ebro Delta, Sentinel-2 showed the potential for the estimation of macrophyte and macroalgae coverage (discrimination capabilities), and its use as environmental proxy for agricultural run-off disturbance, albeit expanding the dataset of field measurements/observations is needed to validate the applied methodology. To improve it, we propose to explore approaches accounting for vegetation leaf area and/or substrate induced variations (Yang and Yang, 2009;Pu et al, 2015), exploiting the spectral peak around 700 nm, which is differently influenced by seagrass types, and it is located beyond the wavelengths usually affected by epiphytes (Hwang et al, 2019).…”
Section: Monitoring Of Submerged Vegetationmentioning
confidence: 99%